# MA101.20 Generalisation of the chain rule to partials

Consider the following simple example. Let f be a function of two variables defined by:

$f(x,y)=x^2 y$ where $x,y \in \mathbb{R}$.

By substituting,

$X = u \cos{v}$
$Y = u + 3v$

Let us define a function F of two variables by $F(x,y) = u^2 \cos{^2}{v}(u + 3v)$

Then we can calculate

$\frac{\partial{F}}{\partial{u}} = 3u\cos{^2}{v}(u+2v)$

With the obvious intentions regarding the partial derivatives $\frac{\partial{f}}{\partial{x}}, \frac{\partial{x}}{\partial{u}}, \frac{\partial{x}}{\partial{u}}, \frac{\partial{y}}{\partial{u}}$ we can also calculate

\displaystyle \begin{aligned} &\frac{\partial{f}}{\partial{x}} \cdot \frac{\partial{x}}{\partial{u}}+\frac{\partial{f}}{\partial{y}} \cdot \frac{\partial{y}}{\partial{u}} \\&= 2xy\cos{v}+x^2\cdot 1 \\&= 2u\cos{v}(u+3v)\cos{u} + y^2\cos{^2}{v} \\&= 3u\cos{^2}{v}(u+2v) \\&= \frac{\partial{F}}{\partial{u}} \end{aligned}

It can also be checked that

\displaystyle \begin{aligned} &\frac{\partial{f}}{\partial{x}} \cdot \frac{\partial{x}}{\partial{v}}+\frac{\partial{f}}{\partial{y}} \cdot \frac{\partial{y}}{\partial{v}} = \frac{\partial{F}}{\partial{v}} \end{aligned}

These two results are indeed true for a general function $f(x,y)$ and substitution $x=x(u,v), y=y(u,v)$. They are regarded as a generalisation of the chain rule for one variable. Again $\frac{\partial{F}}{\partial{u}}$ and $\frac{\partial{F}}{\partial{v}}$ are often confusingly written as $\frac{\partial{f}}{\partial{u}}$ and $\frac{\partial{f}}{\partial{v}}$.

The rule is then

$\displaystyle \frac{\partial{f}}{\partial{u}} = \frac{\partial{f}}{\partial{x}} \cdot \frac{\partial{x}}{\partial{u}}+\frac{\partial{f}}{\partial{y}} \cdot \frac{\partial{y}}{\partial{u}}$

$\displaystyle \frac{\partial{f}}{\partial{v}} = \frac{\partial{f}}{\partial{x}} \cdot \frac{\partial{x}}{\partial{v}}+\frac{\partial{f}}{\partial{y}} \cdot \frac{\partial{y}}{\partial{v}}$

It is very important to remember what is meant by all these items.

Note the chain rule can be used both ways.

ie let $f(x,y)$, $x=x(u,v)$, $y=y(u,v)$ define $F(u,v)$

We have

$\displaystyle \frac{\partial{F}}{\partial{u}} = \frac{\partial{f}}{\partial{x}} \cdot \frac{\partial{x}}{\partial{u}}+\frac{\partial{f}}{\partial{y}} \cdot \frac{\partial{y}}{\partial{u}}$

But also $f(u,v)$ defines $f(x,y)$ (substituting for u and v in terms of x and y)

So,

$\displaystyle \frac{\partial{f}}{\partial{x}} = \frac{\partial{f}}{\partial{u}} \cdot \frac{\partial{u}}{\partial{x}}+\frac{\partial{f}}{\partial{v}} \cdot \frac{\partial{v}}{\partial{x}}$

and, of course, we put F as f throughout.

These results are special cases of the so called general chain rule.

If we have a function $f(x_{1},...x_{n})$ where x are substitutions

$\displaystyle x_1 = \phi (u_{1},...u_{n})$
$\displaystyle x_2 = \phi (u_{1},...u_{n})$
$\displaystyle \vdots$
$\displaystyle x_n = \phi (u_{1},...u_{n})$

Then $\displaystyle \frac{\partial{f}}{\partial{u_1}} = \frac{\partial{f}}{\partial{x_1}} \cdot \frac{\partial{x_1}}{\partial{u_1}}+ \frac{\partial{f}}{\partial{x_2}} \cdot \frac{\partial{x_2}}{\partial{u_1}}+\cdots+ \frac{\partial{f}}{\partial{x_n}} \cdot \frac{\partial{x_n}}{\partial{u_1}}$

###### Special cases

i) $\displaystyle f=f(x,y), x=x(t), y=y(t)$

$\displaystyle \frac{\partial{f}}{\partial{t}} = \frac{\partial{f}}{\partial{x}} \cdot \frac{\partial{x}}{\partial{t}}+\frac{\partial{f}}{\partial{y}} \cdot \frac{\partial{y}}{\partial{t}}$

ii) $\displaystyle f=f(x,y), y=y(x), x=x$

$\displaystyle \frac{\partial{f}}{\partial{x}} = \frac{\partial{f}}{\partial{x}} +\frac{\partial{f}}{\partial{v}} \cdot \frac{\partial{v}}{\partial{x}}$

This site uses Akismet to reduce spam. Learn how your comment data is processed.